Preparation and characterization of polyvinyl alcohol/chitosan composite films reinforced with cellulose nanofiber / Choo Kai Wen - Choo, Kai Wen (2017)
Natural nanocellulose reinforced polymer composites are recently gaining interest in various applications. Much more attentions have been focused to replace petroleum-derived polymers with sustainable natural biopolymers due to their unique properties. In many instances, the fabrication of composites through blending approach of natural and synthetic polymers does not meet the satisfaction on their properties. Thus, the reinforcement of nanofiller into the composite could be a promising way to produce biomaterials with desired properties. The purpose of this project is to discover the effect of cellulose nanofiber (CNF) reinforced on the characteristics of polyvinyl alcohol (PVA)/chitosan (CS) composite. In this study, microcrystalline cellulose (MCC) was oxidized by 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation method. Bio-nanocomposite films were then prepared from PVA/CS polymeric blends with different TEMPO-mediated oxidized cellulose nanofiber (TOCN) contents (0, 0.5, 1.0 and 1.5 wt%) via the solution casting method. The composite films were characterized in terms of crystallinity, morphological, mechanical, chemical and thermal properties. The morphology results from field emission scanning electron microscopy (FESEM) analysis justified that homogenous dispersion of TOCNs was achieved up to 1.0 wt% in the PVA/CS composite. For the tensile profile of pure PVA/CS composite, it was observed that the optimum tensile strength and elongation at break has been achieved in PVA/CS/TOCNs = 75/25/0.5 composite. For the thermal study by thermogravimetric analysis (TGA) and differential thermogravimetric (DTG) analysis, there was improvement of 4°C and 6°C in onset temperature and maximum degradation temperature, respectively when 1.0 wt% of TOCNs was added into the PVA/CS = 50/50 composite. As evidenced by Fourier transform infrared (FTIR) analysis, itshowed the well interaction between the functional groups of TOCNs and PVA/CS composite matrix due to strong hydrogen bonding. Based on the crystallinity study by x-ray diffraction (XRD), the addition of TOCNs has successfully enhanced the molecular ordering in the amorphous phase of the composite. Hence, the improved characteristics of TOCNs reinforced composites could be strongly beneficial in numerous applications in the future. Keywords: bio-nanocomposite films, polyvinyl alcohol, chitosan, TEMPO-oxidized cellulose nanofiber, solution casting.